An extended Canvas business model: A tool for sustainable technology transfer and adoption - Amoussohoui, R.; Arouna, A.; Bavorova, M.; Tsangari, H.; Banout, J. (Elsevier, 2022)
The rise of new agricultural technologies represents an opportunity for agricultural development, especially to achieve the 2030 Sustainable Development Goal. However, farmers in developing countries struggle with adopting new agricultural technologies due to several socio-economic factors. This study proposes a service-based business for transfer and sustainable scaling of new technologies to increase household resilience. Two segments, (i) cost-benefit and (ii) sensitivity analysis was added to the original Canvas business model. We used two innovative technologies: a personalised extension application and a rice threshing machine to apply the business model. Quantitative data from 700 randomly selected rice farmers in Kano State, and qualitative data collected using the Delphi method were used. The adapted Canvas business model is profitable when both technologies are used separately, with an Internal Rate of Return (IRR) of 23 and 28% for the threshing machine and the application, respectively. However, higher profitability is observed when both technologies are combined in one business model. In this case, the business has an IRR of 33%. Moreover, the study shows that the combined business model is vulnerable to the service price. Therefore, we recommend re-evaluating the business model to determine a fair price and payment method for both the service recipient and the provider